2021
DOI: 10.1186/s12974-021-02237-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory resolution and vascular barrier restoration after retinal ischemia reperfusion injury

Abstract: Background Several retinal pathologies exhibit both inflammation and breakdown of the inner blood-retinal barrier (iBRB) resulting in vascular permeability, suggesting that treatments that trigger resolution of inflammation may also promote iBRB restoration. Methods Using the mouse retinal ischemia-reperfusion (IR) injury model, we followed the time course of neurodegeneration, inflammation, and iBRB disruption and repair to examine the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 153 publications
2
52
0
Order By: Relevance
“…102 In this regard, many groups have used pharmacological microglial inhibitors to prevent or protect against retinal degeneration in a variety of murine models of retinal degeneration, including retinal I/R injury, optic nerve damage, and NMDA-induced excitotoxicity. 47,53,59,[103][104][105] In our study, we also found microglial activation with increase in Tlrs, Cd68, Iba1, and Il-1β expressions in the ischemic retina, and administration of pemafibrate modulated pathological microglial activation and further prevented retinal dysfunction. However, as microglia have also been thought to have context-dependent roles (either protective or deleterious to neurons), 106,107 we may F I G U R E 3 Molecular changes by oral administrations of pemafibrate in the ischemic retina 1 day after retinal I/R injury.…”
Section: Discussionsupporting
confidence: 64%
“…102 In this regard, many groups have used pharmacological microglial inhibitors to prevent or protect against retinal degeneration in a variety of murine models of retinal degeneration, including retinal I/R injury, optic nerve damage, and NMDA-induced excitotoxicity. 47,53,59,[103][104][105] In our study, we also found microglial activation with increase in Tlrs, Cd68, Iba1, and Il-1β expressions in the ischemic retina, and administration of pemafibrate modulated pathological microglial activation and further prevented retinal dysfunction. However, as microglia have also been thought to have context-dependent roles (either protective or deleterious to neurons), 106,107 we may F I G U R E 3 Molecular changes by oral administrations of pemafibrate in the ischemic retina 1 day after retinal I/R injury.…”
Section: Discussionsupporting
confidence: 64%
“…Then, a topical antibiotic and steroid ointment (TobraDex; Alcon Laboratories, Inc., Texas, USA) was applied to the conjunctival sac. Eyes with cannulation-induced cataracts, iris/retinal bleeding, or anterior chamber leakage (leaks can be easily detected as dripping and wetting) were excluded [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports from us and others have suggested that reductions in pathologic retinal inflammatory cells could be beneficial for retinal neuronal protection in a murine model of retinal I/R injury [ 13 , 32 , 33 ]. The therapeutic strategy of modulating pathologic inflammatory cells for neuroprotection can be seen in brain injury, rather than just retinal I/R injury [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%